Symmetric Block Algorithm WBC1 and Analysis of Its Implementation Complexity - Igor Baranov (Кібернетика та комп'ютерні технології)
Introduction. Nowadays, computer networks are gaining more and more importance for information exchange. Cryptography plays a vital role in the security of computing, mobile phone communication, passwords in computing and even engineering, unlike in the olden days when cryptography was only about encrypting and decrypting messages with keys. One of the most important requirements of these networks is to ensure the safe transfer of information from one place to another. Cryptography is one of the methods that provide the most secure way of transferring confidential information from the sender to the intended recipient. The work describes the symmetric block cryptographic algorithm WBC1. The article examines the encryption process in detail, analyzes the complexity of the algorithm and the speed of execution. The implementation of the algorithm is shown. The purpose of the work is to describe a new symmetric block cryptographic algorithm WBC1, to investigate its complexity and execution speed. Results. The block symmetric cryptographic algorithm WBC1 was built, the complexity analysis and speed of its execution were studied. The examples show the approbation of the new algorithm. Conclusions. The WBC1 algorithm is a cryptographically stable encryption method that provides a high level of security through the use of complex permutations and cyclic shifts. For large volumes of data, methods and algorithms of parallel and distributed calculations for computers with parallel architecture should be used. the capabilities of the presented algorithm are quite large. And the possibility of increasing the power of the algorithm makes it flexible for use in various areas and spheres of activity related to the processing of information subject to cryptographic protection.